Loss to follow-up tuberculosis treatment and associated factors among adults attending at public health facilities in Warder District, Somali Regional State, Eastern Ethiopia - Birhane, Mohammed; Mekonnen, Shambel; Dingeta, Tariku; Teklemariam, Zelalem (Frontiers in Public Health, 2023)
ABSTRACT Background: Tuberculosis is a major public health problem worldwide, particularly in resource-limited countries. The loss of follow-up during treatment is one of the major obstacles in the fight against tuberculosis, which has serious implications for patients, their families, communities, and health service providers. Purpose: to assess the magnitude of loss to follow-up tuberculosis treatment and associated factors among adults attending public health facilities in Warder District, Somali Regional State, eastern Ethiopia, from November 2, 2020, to November 17, 2021. Methods: A five-year (from January 1, 2016, to December 31, 2020) retrospective study was conducted on 589 adult tuberculosis treatment records. The data were collected using a structured data extraction format. STATA version 14.0 statistical packages were used to analyze the data. Variables with P<0.05 in the multivariate logistic regression analysis were considered statistically significant. Results: Ninety-eight (16.6%) tuberculosis patients failed to follow-up on their treatment. Age 55–64 years (AOR = 4.4, 95% CI: 1.9–9.9), male gender (AOR = 1.8, 95% CI: 1.1–2.9), living 10 kilometers from a public health facility (AOR = 4.9, 95% CI: 2.5–9.4), and a history of tuberculosis treatment (AOR = 2.3, 95% CI: 1.2–4.4) were all associated with a higher likelihood of loss to follow-up, whereas a positive initial smear result (AOR = 0.48, 95% CI: 0.24–0.96) was associated with a lower probability of loss to follow-up. Conclusion: One of six patients were lost to follow-up after the initiation of their tuberculosis treatment. Hence, improving the accessibility of public health facilities with a special focus on the elderly, male patients, smear-negative patients, and retreatment cases are highly warranted among tuberculosis patients. Keywords: Tuberculosis, loss to follow-up, Treatment outcome, Warder, Somalia Region